Performance Measures in Earnings‐Based Financial Covenants in Debt Contracts - LI, NINGZHONG (Journal of Accounting Research, 2016)
ABSTRACT This paper examines how performance measures are defined in major earnings‐based financial covenants in loan contracts to shed light on the economic rationales underlying the contractual use of performance measures. I find an earnings‐based covenant is typically based on a performance measure close to earnings before interest, tax, amortization, and depreciation expenses (EBITDA). However, my empirical analyses show that EBITDA is less useful in explaining credit risk than earnings before interest and tax expenses (EBIT) and even the bottom‐line net income. Thus, measuring credit risk cannot fully explain the choice of accounting performance measures in earnings‐based covenants. I conjecture that contracting parties choose an EBITDA‐related measure, instead of a measure calculated after depreciation and amortization expenses (e.g., EBIT), to make the performance measure less sensitive to investment activities, which can be controlled through other contractual terms, such as a restriction on capital expenditure, and provide empirical evidence consistent with this conjecture.